Exploring hazardous alcohol use and its determinants among health professionals in Bahir Dar, Northwest Ethiopia - Koye, Selam; Tinsae, Techilo; Menberu, Melak; Tareke, Minale (Frontiers in Psychiatry, 2025)
IntroductionAlcohol consumption among health professionals can have serious and multifaceted impacts, affecting both the individual and their professional responsibilities. Despite its critical importance, there is limited research on the burden and contributing factors of hazardous alcohol use among health professionals in Ethiopia. This study aimed to evaluate the magnitude and determinants of hazardous alcohol use among health professionals in Bahir Dar City, Northwest Ethiopia.MethodAn institution-based cross-sectional study was conducted from June 1-30, 2020, involving 384 health professionals. Participants were selected through a simple random sampling method, stratified by profession. Data were collected using a structured and semi-structured self-administered questionnaire, and hazardous alcohol use was assessed using the 10-item Alcohol Use Disorder Identification Test (AUDIT). Data entry was done using EpiData Version 4.6, and analysis was carried out with SPSS Version 23. Bivariable and multivariable logistic regression analyses were employed to estimate crude and adjusted odds ratios, respectively, with a 95% confidence interval. A p-value of less than 0.05 was considered statistically significant.ResultsThe burden of hazardous alcohol use among health professionals was 16.4% (95% CI: 13%-20.3%). Significant factors associated with hazardous alcohol use included having a family history of alcohol consumption (AOR=2.68, 95% CI: 1.27-5.66), mild psychological distress (AOR=2.7, 95% CI: 1.12-6.50), moderate/severe psychological distress (AOR=5.84, 95% CI: 2.08-16.37), lifetime Khat use (AOR=10.44, 95% CI: 3.96-27.53), and possessing a diploma-level education (AOR=3.56, 95% CI: 1.28-9.87).ConclusionThe high prevalence of hazardous alcohol use among health professionals in Bahir Dar City underscores an urgent need for targeted intervention and prevention strategies. Significant risk factors, including family history of alcohol use, psychological distress, Khat use, and educational level. To reduce hazardous alcohol use, the study recommends mental health programs, workplace policies promoting well-being, and integrated prevention and treatment strategies for alcohol and khat use.